2014
DOI: 10.1128/jvi.01347-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of Giant Bacteriophage ϕKZ Is Independent of the Host Transcription Apparatus

Abstract: Pseudomonas aeruginosa bacteriophage KZ is the type representative of the giant phage genus, which is characterized by unusually large virions and genomes. By unraveling the transcriptional map of the ϳ280-kb KZ genome to single-nucleotide resolution, we combine 369 KZ genes into 134 operons. Early transcription is initiated from highly conserved AT-rich promoters distributed across the KZ genome and located on the same strand of the genome. Early transcription does not require phage or host protein synthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
251
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(272 citation statements)
references
References 47 publications
6
251
1
4
Order By: Relevance
“…Initial sequencing of a mixture of the candidates showed the presence of amber mutations in 33 SPN3US genes, 24 with homologs in ϕKZ. Numbers of these 24 genes would also be expected to be essential based on studies of other phages; for instance, the SbcC subunit of T4 was demonstrated to be essential using genetics, and the subunits of the ϕKZ multisubunit RNAPs would be expected to be essential based on the replication of the phage in the presence of rifampin (19). However, to confirm that any of the detected SPN3US amber mutations were actually in an essential gene, each mutation must be identified as the sole amber mutation in an individual genome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial sequencing of a mixture of the candidates showed the presence of amber mutations in 33 SPN3US genes, 24 with homologs in ϕKZ. Numbers of these 24 genes would also be expected to be essential based on studies of other phages; for instance, the SbcC subunit of T4 was demonstrated to be essential using genetics, and the subunits of the ϕKZ multisubunit RNAPs would be expected to be essential based on the replication of the phage in the presence of rifampin (19). However, to confirm that any of the detected SPN3US amber mutations were actually in an essential gene, each mutation must be identified as the sole amber mutation in an individual genome.…”
Section: Discussionmentioning
confidence: 99%
“…Two multisubunit RNAPs are considered hallmark features of phages related to ϕKZ, with every member containing two sets of subunits (19), one set presumably arising from a gene duplication event(s) after becoming phage borne. This is quite remarkable considering that the two subunits (β and β′) themselves are hypothesized to have arisen from an ancient duplication event (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). Phage early mRNA shutdown has been reported in T7 (45) and in the phage PhiKZ; early mRNA shutdown is observed after the early stage of infection (46). Probes G, H, I, J, and K detected 11 middle mRNAs covering the leftward-oriented cluster in the right arm of the genome (Fig.…”
Section: Resultsmentioning
confidence: 81%